Chronic Alcohol Dysregulates Glutamatergic Function in the Basolateral Amygdala in a Projection-and Sex-Specific Manner - Price, Michaela E.; McCool, Brian A. (Frontiers in Cellular Neuroscience, 2022)
Chronic intermittent ethanol and withdrawal (CIE/WD) produces alcohol dependence, facilitates anxiety-like behavior, and increases post-CIE alcohol intake. The basolateral amygdala (BLA) is one of several brain regions that regulates anxiety-like behavior and alcohol intake through downstream projections to the nucleus accumbens (NAC) and bed nucleus of the stria terminalis (BNST), respectively. Previous studies revealed that CIE/WD induces input- and sex-specific adaptations to glutamatergic function in the BLA. The BLA receives information from two distinct input pathways. Glutamatergic afferents from medial structures like the thalamus and prefrontal cortex enter the BLA through the stria terminalis whereas lateral cortical structures like the anterior insula cortex enter the BLA through the external capsule. CIE/WD increases presynaptic glutamatergic function at stria terminalis synapses and postsynaptic function at external capsule synapses. Previous studies sampled neurons throughout the BLA, but did not distinguish between projection-specific populations. The current study investigated BLA neurons that project to the NAC (BLA-NAC neurons) or the BNST (BLA-BNST neurons) as representative “reward” and “aversion” BLA neurons, and showed that CIE/WD alters glutamatergic function and excitability in a projection- and sex-specific manner. CIE/WD increases glutamate release from stria terminalis inputs only onto BLA-BNST neurons. At external capsule synapses, CIE/WD increases postsynaptic glutamatergic function in male BLA-NAC neurons and female BLA-BNST neurons. Subsequent experiments demonstrated that CIE/WD enhanced the excitability of male BLA-NAC neurons and BLA-BNST neurons in both sexes when glutamatergic but not GABAergic function was intact. Thus, CIE/WD-mediated increased glutamatergic function facilitates hyperexcitability in male BLA-NAC neurons and BLA-BNST neurons of both sexes.